(untitled) (Bangladesh Journal of Animal Science, 2022)
Semen production from breeding bulls used in Artificial Insemination (AI) program is of great importance in cattle breeding. Good quality semen has positive effect on the fertility of cows and heifers. The aim of this study was to evaluate the quality and assessed as the freezing ability of Red Chittagong Cattle (RCC) bull with fresh-diluted semen and frozen semen. The parameters of semen characteristics included were volume per ejaculate (ml), percentage of mass motility, normal and abnormal sperm, and sperm concentration (million/ml). The highest mass motility was found in bull ID No. 4 and the lowest in bull ID No. 1 but the highest sperm concentration was found in bull ID No. 3 with lowest in bull ID No. 2 in fresh semen. Highly significant (p<0.001) positive correlation was found between mass motility and sperm concentration in bulls of ID No. 3 and 4, a negative significant (p<0.05) correlation was found between mass motility and normal sperm percentage. Two freezing techniques were followed in frozen semen production: Cork sheet freezing and Cryobath freezing with two freezing times 15 and 30 minutes were also applied. Variations in the motility of frozen semen by Cork sheet freezing with two different times were found significant (p<0.05) between bulls. Furthermore, highly significant (p<0.01) difference of motility by Cryobath freezing was found between the bulls. The highest motility after both 15 and 30 minutes Cork sheet freezing and Cryobath freezing was found in bull ID No. 4 and lowest in bull ID No. 3. In the present study, variability in the potentiality of bulls (semen volume and sperm concentration) was observed and found lower than crossbred bulls due to small size of Red Chittagong, an indigenous zebu cattle of Bangladesh. Bangladesh Journal of Animal Science. 51(1):25-30